Dispersão de Biomphalaria straminea, hospedeira intermediária do Schistosoma mansoni, através da distribuição de peixes The spreading of Biomphalaria straminea, intermediate host of Schistosoma mansoni through the distribution of fishes - Renato de R. Corrêa; José Maurício de Toledo Murgel; José de Toledo Piza; Alberto da Silva Ramos; Luiz Cândido de Souza Dias; Lúcia Vieira C. Morais; Felipe Francisco do Rosário (Universidade de São Paulo, 1970)
Foi focalizado, pela primeira vez o encontro de B. straminea no Estado de São Paulo. Esta espécie vem juntar-se aos planorbídeos já assinalados em nosso Estado. Foram descritos os criadouros, onde a B. straminea foi coletada, localizados em tanques de criação de peixes nas Estações de Piscicultura de Barra Bonita e Americana, Estado de São Paulo, e em um aquário particular na capital dêsse Estado. Fêz-se referência ao transporte de peixes oriundos de zonas do país onde ocorre aquela espécie, Amazonas e Ceará, como responsável pela introdução daquele molusco no Estado. Destacou-se êsse achado pelo perigo que representa a distribuição de peixes da maneira como vem sendo feita atualmente em nosso país, tendo sido julgado necessário o estabelecimento de quarentena para aquêles vindos de zonas infestadas por espécies hospedeiras intermediárias do S. mansoni. Foram relatadas as medidas de combate aos caramujos efetuadas imediatamente após aquela descoberta e os resultados obtidos. Conclui-se que a dispersão passiva da B. straminea pelo transporte de peixes, deve ampliar a distribuição geográfica dêsse planorbídeo, já assinalado na Venezuela, Guianas e no Brasil, sendo que neste último ocorre em tôdas as Unidades Federativas, exceto, no Rio Grande do Sul, Santa Catarina, Rio de Janeiro e Territórios. Up the present, the works of collecting planorbids done in 226 municipalities for the elaboration of the geographical distribution chart in the State of São Paulo (Brazil), showed the presence of two intermediate host species of Schistosoma mansoni: Biomphalaria tenagophila and Biompralaria glabrata. Although the technicians from the Psiculture Stations, have not found snails in the water inside the containers used for the transportation of fishes, the ecological conditions of B. straminea in the latest researches are such as to indicate that they have been introduced, in our State through fish transportation imported from areas where it occurs, such as the State of Amazonas and Ceará (Brazil). The aim of the importation of these fishes is its adaptation to local waters. The occurrence was noticed in the Psiculture Stations of the towns of Barra Bonita and Americana, and in an aquarium of a private house in the city of São Paulo. This shows the danger that the distribution of fishes represents and the way it is being done. The seriousness of the problem originates not only from the importation of the said species but also from its dissemination in the State, through the redistribution to the private Psiculture Stations. It should be remembered that this dissemination can be also done through rivers in which banks are located tanks for the breeding of fishes as mentioned before. This facts was communicated to the National Department of Rural Endemies for the necessary measures. One of the steps to be taken should be the quarentine for fishes from zones infested with species of planorbids hosts of S. mansoni. The passive scattering of B. straminea by the transportation of fishes, will enlarge the geographical distribution of these planorbids,which have already been found in Venezuela, Guianas and Brazil. In this last country it is found in all its States with the exception of Rio Grande do Sul, Santa Catarina, Rio de Janeiro and Federal Territories. Two hundred and seventeen specimens of B. straminea were examined and all of them were negative to cercaries of Shistosoma mansoni.